Selektor Garuk - Gondo Puspito (Maspari Journal : Marine Science Research, 2012)
ABSTRACTThe objective of this study is to obtain a slope of selector that giving the best selectivity to cockle Anadara granosa and Anadara antiquata. Selector was constructed of a line of wood grids with 1 cm in diameter. Gap width between grids was adjusted to the thickness of economical valued cockle Anadara granosa. While, the slopes of selector were α = 10, 20 and 30o. In this study, a number of 120 shells of cockle Anadara granosa and 120 shells of cockle Anadara antiquata were dropped onto selector. Calculation of selector selectivity depended on the retained shells and released shells. Dredge selector was expected to release the shells with length less than 40 mm. Result showed that the selector with slope of 20o was more selective than the other two slopes. Selection length value P50 of cockle Anadara granosa and Anadara antiquata were 39,96 mm and 37,65 mm.Key words : Anadara granosa and Anadara  antiquate, dredge, selector, slope ABSTRAKPenelitian ini bertujuan untuk menentukan sudut kemiringan selektor garuk  yang memberikan nilai selektivitas terbaik untuk kerang darah (Anadara granosa) dan kerang bulu (Anadara antiquata). Selektor tersusun atas sederet batang kayu berdiamater 1 cm. Jarak antar kisi disesuaikan dengan ketebalan cangkang kerang darah yang bernilai ekonomi. Adapun sudut kemiringan selektor α = 10, 20 dan 30o. Dalam penelitian ini, 120 cangkang kerang darah dan 120 cangkang kerang bulu dijatuhkan ke atas selektor.  Perhitungan selektivitas didasarkan atas cangkang kerang yang lolos dan tertahan oleh selektor. Selektor diharapkan meloloskan cangkang kerang darah dan kerang bulu dengan panjang kurang dari 40 mm. Hasilnya menunjukkan bahwa selektor dengan sudut kemiringan a = 20o lebih selektif dibandingkan dengan kedua sudut kemiringan lainnya. Nilai selection length P50 cangkang kerang darah dan kerang bulu pada selektor dengan sudut a = 20o adalah 39,96 mm dan 37,65 mm.Kata kunci: garuk,  kerang darah dan kerang bulu, selektor,  sudut kemiringan